Peran Guru PAK dalam Menerapkan Pembelajaran Inklusif Berbasis Kasih - Tonis, Desi Sriyanti; Gamerakai, Sebayanti; Kii, Selviana Ina; Tapilaha, Sandra Rosiana (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
Cultural, ethnic, and religious diversity can create a unique educational landscape and demand an inclusive and responsive approach. In multicultural schools, the curriculum often intersects with multicultural education, which includes teaching about different cultures, history, global perspectives. The subjects taught not only focus on traditional academics but also must involve content that deeply understands how diversity influences thinking and action. To fulfill learning so that it can influence students' thinking and actions or attitudes, one of the things needed is to create inclusive education based on love. Inclusive education is one type of approach used in the world of education with an emphasis on the importance of acceptance and appreciation of diversity. In the implementation of inclusive education, the role of teachers is needed, one of which is a Christian religious education teacher. The role needed is how teachers apply compassion to students. Teachers can do this through teaching inclusive attitudes, loving attitudes, and teachers must also be role models. The purpose of inclusive education based on love is to carry out learning activities such as role playing, group discussions, and collaborative activities to help children develop attitudes, social skills, and emotions. In discussing the role of Christian religious education teachers in implementing inclusive learning based on love, the method used is a literature approach by collecting information from books and journals based on the discussion.